Intestinal Surgery in Gynecologic Oncology: Are We Training for the Future?. Issue 5 (June 2018) - Connor, Elizabeth V.; Moulton, Laura J.; Costales, Anthony B.; Vargas, Roberto; Michener, Chad M.; AlHilli, Mariam M.
Abstract : Objective: The objective of this study was to assess the scope of intestinal surgery training across gynecologic oncology fellowships in the United States and identify factors associated with perceived preparedness to perform intestinal surgery independently. Materials/Methods: An institutional review board–approved survey was distributed to Society of Gynecologic Oncology fellows and candidate members within the first 3 years of practice. Questions addressed demographics, operative experience, preparedness and plans for performing intestinal surgery, and attitudes toward gynecologic oncologists (GOs) performing intestinal surgery. Responses were analyzed using descriptive statistics as well as univariate and multivariate analyses. Results: Of 374 Society of Gynecologic Oncology members invited, 108 (29%) responded, including 38 fellows (35%) and 53 recent graduates (49%). Fifteen (14%) reported more than 3 years of practice and were excluded. Most participants (96%) received intestinal surgery training from GOs, and 64% reported that all faculty routinely performed intestinal surgery. Most participants (81%) believed GOs should perform intestinal procedures, whereas only 58% felt prepared and 59% planned to perform intestinal procedures independently. Fellows who performed more than 10 intestinal diversion procedures, participated directed in intestine-related intraoperative consultations, or reported that all faculty performed intestinal surgery were more likely to feel prepared to perform intestinal surgery independently. Sex, training region, intended practice environment, and fellowship curriculum were not associated with preparedness to perform intestinal surgery. Conclusions: Almost half of gynecologic oncology fellows and recent graduates in the United States do not feel prepared to perform intestinal procedures independently after fellowship. Increased volume and direct involvement of fellows in intestinal surgery may improve preparedness for performing intestinal surgery after fellowship. Abstract : Supplemental digital content is available in the text.